Análisis de las Características del Estilo Cinematográfico de Hayao Miyazaki (2016)
This work seeks , as its main objective , analyze the characteristics of cinematic style of Hayao Miyazaki, Japanese director of animated films , was applied as a method of harvesting a matrix for each specific objective , they used to analyze four films , all directed with original screenplay Hayao Miyazaki. Since the stylistics of Charles Bally , which states that it is a study of expressive and emotional features of language , it was concluded that Miyazaki expressed narratively culture and ideology as the main concept , then part of a more artistic notion , adding and mixing fantasy with reality , ie making cultural processes and gives them a treatment from the innocent perspective of a child , also concludes with messages to social problems currently living through metamorphosis living the protagonists of the movies